Nonformal Cultural Education, the Preservation of Benjang, and Cultural Awareness: A Case Study of Sekolah Benjang Indonesia - Putri Permata Amir; Siti Komariah; Mirna Nur Alia Abdullah (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
This study examines the nonformal education strategies implemented at Sekolah Benjang Indonesia (Indonesian Benjang School) to preserve Benjang, a traditional art form associated with Ujung Berung, Bandung City, and to explore their contribution to cultural awareness among participants. The study employed a qualitative case study design. Data were collected from seven informants, comprising the founder of the Wallagri Foundation, the school principal, a Benjang trainer, two students, and two community members. Data collection involved in-depth interviews, direct observation, document analysis, and visual documentation of training sessions, public performances, cultural outreach activities, and the school’s launching event. The data were analyzed through reduction, display, and conclusion drawing or verification, supported by source triangulation, technique triangulation, and member checking. The findings show that Sekolah Benjang Indonesia organizes cultural preservation through institutional goal-setting, a staged curriculum based on Panca Niti Atikan Sunda (a Sundanese educational framework), regular training, public performances, ceremonial activities, and the Nyeni di Sakola (arts in schools) outreach program. These activities provided students with opportunities to develop knowledge of the history and cultural meaning of Benjang, artistic skills, responsibility, and self-confidence. Public programs also expanded the visibility of Benjang in community and school settings, while creating opportunities for cultural participation and local support. Public performances further generated temporary opportunities for informal vendors and community networks, representing a latent social consequence of cultural activities. The study concludes that nonformal cultural education can support the continuity of Benjang by connecting cultural knowledge, artistic practice, public participation, and institutional collaboration. The findings are limited to one institutional setting and should not be generalized beyond the participants and context examined.